2014
DOI: 10.1001/jama.2013.285113
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Treatment With Varenicline for Smoking Cessation in Patients With Schizophrenia and Bipolar Disorder

Abstract: IMPORTANCE It is estimated that more than half of those with serious mental illness smoke tobacco regularly. Standard courses of pharmacotherapeutic cessation aids improve short-term abstinence, but most who attain abstinence relapse rapidly after discontinuation of pharmacotherapy.OBJECTIVE To determine whether smokers diagnosed with schizophrenia and bipolar disease have higher rates of prolonged tobacco abstinence with maintenance pharmacotherapy than with standard treatment. DESIGN, SETTING, AND PARTICIPAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
195
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(208 citation statements)
references
References 30 publications
7
195
1
5
Order By: Relevance
“…Prior studies using extended treatment (6 months or more) have demonstrated the utility of maintenance treatment with a single medication, such as NRT 76 or varenicline, 77 once a smoker with schizophrenia has attained an initial period of abstinence. In addition, a prior open-label study with CBT (for 12 weeks), bupropion, and NRT for 1 year demonstrated the feasibility of this approach, with a substantial quit rate of 23.5%, 78 but no control group using TAU.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies using extended treatment (6 months or more) have demonstrated the utility of maintenance treatment with a single medication, such as NRT 76 or varenicline, 77 once a smoker with schizophrenia has attained an initial period of abstinence. In addition, a prior open-label study with CBT (for 12 weeks), bupropion, and NRT for 1 year demonstrated the feasibility of this approach, with a substantial quit rate of 23.5%, 78 but no control group using TAU.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Psychiatric providers are ideally positioned to treat patients who smoke for nicotine dependence during routine office visits. However, psychiatrists and psychiatric nurse practitioners generally lack basic training regarding evidence-based treatment for nicotine dependence, and, in addition to knowledge and skills barriers, they may harbor attitudinal barriers to treating nicotine dependence.…”
Section: Introductionmentioning
confidence: 99%
“…For example, varenicline has shown to result in significantly higher rates of abstinence in smokers with SUD 3 and 6 months after starting it (Rohsenow et al, under review), suggesting that CV plus varenicline might be an effective way to increase both initial abstinence and maintenance of abstinence in smokers with SUD, particularly since varenicline reduces relapse rate in smokers attaining initial abstinence (Evins et al, 2014;Tonstad et al, 2006). Since higher levels of withdrawal discomfort predict less smoking abstinence during and after CV for smokers with SUD (Rohsenow, Tidey, Kahler, Martin, Colby, & Sirota, 2015), combining voucher-based smoking treatments with other pharmacotherapies that reduce craving or withdrawal are likely to increase withintreatment abstinence during CV, as the present results suggest.…”
Section: Discussionmentioning
confidence: 99%